BEVERAGE LIGHTLY CARBONATED WITH LEMONGRASS - Araldi, Edimar Zortea; Araldi, Lenir Zago; Buffon, Karina; de Souza, Edson Luiz; Gelinski, Jane; Soares, Fabiana Andreia A. S. M. (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
In recent years, there is a growing interest in nutraceuticals which provide health benefits and are alternative to modern medicine. Nutrients, herbals and dietary supplements are major constituents of nutraceuticals which make them instrumental in maintaining health, act against various disease conditions and thus promote the quality of life. Lemongrass (Cymbopogon citratus) has been used as a modulator of mood and cognitive function, with anxiolytic and antibacterial effect.  The aim of this work was to develop an innovative, non-dairy, functional beverage using herbal Lemon Balm extract as a natural ingredient which would also be antioxidant and anti-inflammatory capacity. It was used for the preparation of based a lemongrass infusion. Several based grouts were tested to produce a drink with a reduced sugar content. a pickle basis of sucrose and sucralose, which was prepared with heating at 85°C /15min was used. As additives were used malic acid, ascorbic acid and sodium benzoate. It was added to ice water cooling until it reaches 0˚C. We analyze physicochemical property, microbiological for 35 days and sensory evaluation on the 21 days of the final product. Thus, from the results, the product was characterized: total acidity = 0.01g/100mL, pH 3.9, soluble solids: 8.6 °Brix and absence of microbiological standard. The sensory results of this beverage showed greater preference and acceptability index. Given the general acceptance of the product, technical feasibility and quality, it is considered timely to enter the same market.